Immunohistochemical localization of mouse testis-specific phosphoglycerate kinase (PGK-2) by monoclonal antibodies. - Blüthmann, H (1982)
Monoclonal antibodies against mouse testis-specific phosphoglycerate kinase (PGK-2) were produced in order to determine immunohistochemically the onset of PGK-2 synthesis in the germinal epithelium of the mouse. PGK-2 was detected in testis sections in spermatids as early as stage 12 and in spermatozoa, but not in earlier stages of spermatogenesis nor in any somatic cells of the testis. During ontogeny, PGK-2 appears within the testis at day 30 post-partum, concomitant with spermatids entering the maturation phase. All three allelic isozymes PGK-2A, -2B, and -2C were detected equally by the monoclonal antibody in testis sections of several inbred mouse strains, each of which expresses a specific PGK-2 variant. Moreover, the monoclonal antibody against mouse PGK-2 reacted with heterologous sperm-specific PGK from rat, rabbit, and bull and, therefore, may serve as a useful immunochemical marker for mammalian spermatogenesis.